The Effectiveness of Emotional Intelligence Training on Aggression and Hyperactivity of Students with Physical Disability - Khadijeh Fathi; Narges Adib-Sereshki; Firouzeh Sajedi (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Emotional intelligence has an important role on mental and social health of children and its defect prompts children for many problems. The aim of this study was to investigate the effectiveness of emotional intelligence training on reducing aggression and hyperactivity of girl students with physical disability. Materials & Methods: This study was experimental and؛ Pre-test post-test with control group was used. The samples were 40 physically disabled girl' students with behavior disorders whom were in3rd, 4th and 5th grades. The instrument Rutter behavioral questionnaires (the teacher and parent forms). Was used to measure behavior problems. Spss was used for data analysis. Results: The emotional intelligence training reduced the aggression and hyperactivity of students. The pre-testو post-test results by teachers (P<0.001, f=15.04) and parents (P<0.001, f=21.15) Forms have shown a significant differences between the two groups of students in aggression and hyperactivity. Conclusion: It was shown that training of emotional intelligence to physically disabled students with aggression and hyperactivity can help them to improve their behavioral status.